2019
DOI: 10.1016/j.ebiom.2019.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antiviral - passive - active immunization (“sandwich”) therapeutic strategy for functional cure of chronic hepatitis B in mice

Abstract: a b s t r a c tBackground: Chronic Hepatitis B (CHB) remains a major problem for global public health. Viral persistence and immune defects are the two major reasons for CHB, and it was hypothesized that based on a transient clearance of serum viral DNA and HBsAg "window stage", active immunization against hepatitis B virus (HBV) might initiate effective host immune responses versus HBV to achieve functional cure of CHB. Methods: Two experimental mouse models that mice hydrodynamic injected HBV DNA or infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…(15,16) The mechanism relies in the theory that high HBsAb levels would neutralize the potential viral antigen coming from the HBcAb-positive grafts. (17,18) We adopted this strategy and showed similar results that a titer of HBsAb ≥ 1000 IU/L at the time of transplantation delayed the decay of HBsAb titer after transplantation and was associated with lower risk of de novo HBV infection in our pediatric population. However, the blood loss and transfusion during LT and the use of immunosuppressive agents led to the decay of HBsAb titer after transplantation.…”
Section: Original Article | 103mentioning
confidence: 86%
“…(15,16) The mechanism relies in the theory that high HBsAb levels would neutralize the potential viral antigen coming from the HBcAb-positive grafts. (17,18) We adopted this strategy and showed similar results that a titer of HBsAb ≥ 1000 IU/L at the time of transplantation delayed the decay of HBsAb titer after transplantation and was associated with lower risk of de novo HBV infection in our pediatric population. However, the blood loss and transfusion during LT and the use of immunosuppressive agents led to the decay of HBsAb titer after transplantation.…”
Section: Original Article | 103mentioning
confidence: 86%
“…In agreement with their immune effector functions, several studies have demonstrated that administration of neutralizing HBV antibodies in multiple HBVpersistent infection mouse models significantly reduced or depleted HBV virions and subviral particles in blood (73)(74)(75)(76). In particular, depletion of circulating HBsAg in AAV-HBV transduced mice enabled the induction of HBV-specific B and T cell immune responses by distinct vaccination strategies (57,77). Clinically, several human monoclonal antibodies against HBsAg had been shown to significantly reduce viral load and HBsAg antigenemia (72,78).…”
Section: Therapeutic Potential Of Monoclonal Antibodies For Chbmentioning
confidence: 88%
“…The “sandwich” strategy combines an anti-HBsAg neutralizing antibody with an antiviral drug followed by vaccines for specific active immunization ( 36 ). Shi et al have proven that this strategy has the potential to achieve a functional cure for HBV infection ( 26 ). The potential application of mL (G12-IgG) in the combination therapy for HBV infection was underlined by its sustained and progressive effect on reducing HBsAg levels.…”
Section: Discussionmentioning
confidence: 99%
“…Various therapies targeting innate immunity and HBV-specific immune responses are under clinical investigation ( 24 ). Among these medications, anti-HBsAg antibodies are potent candidates ( 25 27 ). Antibody therapies against HBsAg remarkably reduced circulating HBsAg and HBV DNA levels in several mouse models and restored adaptive immunity functionality that was defective due to CHB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation